Optimal mortgage refinancing a closed form solution - Agarwal, Sumit 1970-; Driscoll, John C. 1969-; Laibson, David I. 1966- (National Bureau of Economic Research, 2007)
We derive the first closed-form optimal mortgage refinancing rule. The expression is derived by using the Lambert-W function to solve a tractable class of mortgage refinancing problems. We calibrate our solution and show that our quantitative results closely match those reported by researchers who use numerical methods.
Literaturverz. S. 31 - 34